Peritraumatic distress, pre-existing diseases and medication intake in physicians in face-to-face activity during the COVID-19 pandemic in the city of Lima, Perú - Arévalo Flores, Martín (2024)
Objective: To determine the relationship and connecting factors between pre-existing diseases, medication intake and peritraumatic distress in physicians in face-to-face activity in the city of Lima, Peru during the COVID-19 pandemic. Method: The study included physicians working in the first line of care of patients with COVID-19, as well as physicians working in other areas. The instruments used were the COVID-19 related Peritraumatic Distress Index (CPDI), Patient Health Questionnaire-9 (PHQ-9), and Generalized Anxiety Disorder Scale-7 (GAD-7). A general linear model was performed taking the CPDI values as the dependent variable to assess distress-related factors. Results: 288 physicians were included, 54.50% of whom worked in the front line. The CPDI value showed a direct relationship with GAD-7 and PHQ-9, as well as with medical illness. A statistically significant direct relationship was also found with the interaction between the variables "frontline", "medical illness" and "medication intake". A post-hoc analysis showed greater distress in non-frontline doctors who had an illness and were taking medication, compared to doctors in the same occupational group without illness and who were not taking any medication. Likewise, greater distress was found in front-line doctors who had an illness and were not taking any medication. Conclusions: Distress values for COVID-19 in physicians were directly related not only to anxiety and depression values, but also to the presence of medical illness. Additionally, the joint occurrence of a medical illness and medication treatment was associated with elevated COVID-19 distress values in non-frontline physicians.